Adverse Effect of Topical Fluorinated Corticosteroids in Rosacea. Issue 5645 (15th March 1969) - Sneddon, Ian
Abstract : Fourteen patients suffering from rosacea treated by prolonged topical applications of fluorinated steroids showed adverse effects. Aggravation and extension of telangiectasia occurred in all, and in most cessation of the treatment was followed by severe rebound inflammatory oedema and acute pustular eruption. The telangiectasia cleared or was much improved within three months of cessation of the use of fluorinated steroids. Hydrocortisone did not produce the same effect, and hence it was used, together with oral tetracycline, for treatment.